I've got algorithm: predicting tumor and autoimmune peptide targets for [CD8.sup.+] T cells - Dersh, Devin; Yewdell, Jonathan W (The Journal of clinical investigation, 2016)
[CD8.sup.+] T cells play a central role in eradicating intracellular pathogens, but also are important for noninfectious diseases, including cancer and autoimmunity. The ability to clinically manipulate [CD8.sup.+] T cells to target cancer and autoimmune disease is limited by our ignorance of relevant self-peptide target antigens. In this issue of the JCI, Pearson et al. describe 25,270 MHC class l-associated peptides presented by a wide range of HLA A and B allomorphs expressed by 18 different B cell lines. Via extensive bioinformatic analysis, the authors make surprising conclusions regarding the selective nature of peptide generation at the level of individual gene products and create a predictive algorithm for disease-relevant self-peptides that will be of immediate use for clinical and basic immunological research.